Detection of various beta lactamases in gram negative bacteria and their resistance pattern in northern India - Ashish Khanna; Menka Khanna; Sarabjit Sharma (Tropical Journal of Pathology and Microbiology, 2019)
Background: Resistance to broad spectrum beta lactam antibiotics due to ESBL/AmpC/MBL enzymes is an increasing problem worldwide. Estimation of their prevalence in the area is essential to formulate an effective antimicrobial policy for a particular hospital/area. Aim: The present study was done to know the prevalence of ESBL/AmpC/MBL in gram negative organisms isolated from clinical samples and their susceptibility pattern in a tertiary care hospital in northern India. Methods: Total of 160 isolates of gram negative organisms from clinical specimens were screened for the presence of various beta lactamases by standard phenotypic methods and their antibiotic susceptibility pattern to conventionally used antibiotics was determined by disc diffusion method as per CLSI guidelines. Results: 118 gram negative isolates showing reduced susceptibility to third generation cephalosporin’s were screened for ESBL/ AmpC/ MBL production. Beta lactamase production was seen in 74 out of the 160 gram negative isolates obtained from different samples. ESBL production alone or in combination with AmpC/MBL is seen in 60 isolates. ESBL/ AmpC and ESBL/ MBL coproduction was seen in 9(5.6%) and 3(1.9%) of the isolates respectively. Multi drug resistance was significantly higher in beta lactamase producers than non lactamase producers. Conclusions: There is need for continuous surveillance in the hospitals for the detection of various beta lactamases or resistant strains. Strict guidelines should be followed for antibiotic therapy so as to reduce burden of antibiotic resistance. Further phenotypic and genotypic studies should be undertaken to know the resistance pattern in bacteria.